P0490IS THE SEVERITY OF GLOMERULAR IGG STAINING IN PATIENT WITH IGA NEPHROPATHY USEFUL FOR PREDICTING POOR RENAL PROGNOSIS? THE DATA FROM TSN-GOLD WORKING GROUP. (6th June 2020) - Turgutalp, Kenan; Cebeci, Egemen; Turkmen, Aydin; Derici, Ülver; Seyahi, Nurhan; Eren, Necmi; Dede, Fatih; Gullulu, Mustafa; Basturk, Taner; Manga Sahin, Gulizar; Yılmaz, Mürvet; Sipahi, Savas; et al.
Abstract: Background and Aims: In IgA nephropathy (IgAN), which is characterized by mesangial IgA accumulation, there is the formation of circulating autoantibodies against galactose deficient IgA1s (Gd-IgA1). IgG / Gd-IgA1 immunocomplexes accumulate in the glomerular mesangium and play a role in the pathogenesis of IgAN. Recent studies have suggested a relationship between glomerular IgG deposition and the severity of glomerular inflammation. However, detection of the presence and severity of IgG in routine immunofluorescence microscopy (IFM) may fail. This study aims to investigate whether IgG positivity detected by IFM is associated with poor renal prognostic indicators and whether renal prognosis can be predicted according to IgG positivity. Method: 4399 patients who were enrolled between May 2009-June 2019 in database of Turkish Society of Nephrology, Glomerular Diseases Working Group (TSN-GOLD) including 44 centers were evaluated. After exclusion criteria, 994 primary IgAN patients were included in the study. Glomerular IgG negative and positive patients were compared by means of Oxford classification scores, histopathological evaluations, proteinuria, creatinine, albumin, blood pressures. IgG positive patients were divided into subgroups according to the grade of the IFM positivity. The relationship between IgG positivity and poor prognosis criteria were evaluated. Results: Demographic and biochemical findings of glomerular IgG positive and negative patients at the time of biopsy are shown in Table 1. No difference was found between the groups. There was no difference in the demographic and biochemical findings at the time of biopsy in IgG subgroup analyses (Table 2). There was no difference between the histopathological and Oxford MEST scores of the subgroups. Glomerular IgG positivity was not associated with diastolic blood pressure, systolic blood pressure, urea, uric acid, age, eGFR, albumin, proteinuria (p> 0.05 for all, r= -0.084, r= -0.102, r= -0.006, r=0.062, r= 0.014, r= -0.044, r= -0.061, r= -0.066, r= 0.150, respectively). Conclusion: Glomerular IgG positivity detected by routine IFM in IgAN is not associated with poor renal prognostic indicators. It is difficult to predict renal prognosis by looking at the severity of IgG positivity at the baseline evaluation.